2021
DOI: 10.3390/molecules26071865
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Galantamine-Curcumin Hybrid as a Potential Multi-Target Agent against Neurodegenerative Disorders

Abstract: The acetylcholinesterase (AChE) inhibitors are the main drugs for symptomatic treatment of neurodegenerative disorders like Alzheimer’s disease. A recently designed, synthesized and tested hybrid compound between the AChE inhibitor galantamine (GAL) and the antioxidant polyphenol curcumin (CU) showed high AChE inhibition in vitro. Here, we describe tests for acute and short-term toxicity in mice as well as antioxidant tests on brain homogenates measured the levels of malondialdehide (MDA) and glutathione (GSH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…The similar effects suggest a similar mode of action— 4b might act as an allosteric modulator of α7 nAChRs. Recently, we found that 4b is a low-toxic compound (LD 50 in mice was 49 mg/kg), inhibits AChE in vivo and in vitro better than GAL, and demonstrates high antioxidant activity in vitro and ex vivo outperforming the activities of both GAL and CU [ 21 ]. Together with the findings in the present study, 4b has emerged as a promising multi-target agent for a complex treatment of neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar effects suggest a similar mode of action— 4b might act as an allosteric modulator of α7 nAChRs. Recently, we found that 4b is a low-toxic compound (LD 50 in mice was 49 mg/kg), inhibits AChE in vivo and in vitro better than GAL, and demonstrates high antioxidant activity in vitro and ex vivo outperforming the activities of both GAL and CU [ 21 ]. Together with the findings in the present study, 4b has emerged as a promising multi-target agent for a complex treatment of neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…As GAL derivatives, compounds 4b and 8 were expected also to reduce the toxic effects of Aβ. As the present study was a continuation of our previous research [ 16 , 21 ], we preferred to keep the original compound IDs.…”
Section: Introductionmentioning
confidence: 99%
“…It is a new IAChE, which is a combination of galantamine and curcumin. In ex vivo tests, the fusion of the two compounds is more effective than their separate administration [ 239 ]. This combination is based on the strong antioxidant properties of curcumin and the AChE inhibitory activity of galantamine [ 240 ].…”
Section: Antioxidants As the Prevention And Treatment Of Depression And Admentioning
confidence: 99%
“…Galantamine (GAL) is one of the most widely prescribed drugs for treating AD [13]. Apart from being an AChE inhibitor, GAL is an allosteric modulator of nicotinic ACh receptor [14], has antioxidant properties [15] and facilitates the clearance of Aβ peptide in rat brains [16]. Due to this variety of actions, GAL can serve as а multitarget scaffold to design new derivatives with a higher AChE inhibitory effect and lower toxicity.…”
Section: Introductionmentioning
confidence: 99%